Setting of import tolerances for oxathiapiprolin in various crops. (16th June 2020) - ,; Anastassiadou, Maria; Bernasconi, Giovanni; Brancato, Alba; Carrasco Cabrera, Luis; Greco, Luna; Jarrah, Samira; Kazocina, Aija; Leuschner, Renata; Magrans, Jose Oriol; Miron, Ileana; Nave, Stefanie; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Du Pont (UK) submitted a request to the competent national authority in the United Kingdom to set an import tolerance for the active substance oxathiapiprolin in various crops in support of authorised uses in the United States. The data submitted in support of the request were found to be sufficient to derive maximum residue level (MRL) proposals for citrus fruits, blackberries, raspberries, Chinese cabbage, basil and edible flowers and asparagus. For dewberries, potatoes and sweet potatoes, data gaps were identified which precluded the derivation of MRL proposals. Adequate analytical methods for enforcement are available to control the residues of oxathiapiprolin in plant matrices at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the long‐term intake of residues resulting from the use of oxathiapiprolin according to the reported agricultural practices is unlikely to present a risk to consumer health.